A Many-Eyed Lens in Counselling Practice With Indigenous People: An Innovative Path Towards Reconciliation and Rippling - Kauffman, Theresa (Canadian Journal of Counselling and Psychotherapy, 2024)
As counselling practitioners navigate through the 21st century, holding and integrating multiple views in counselling practice with Indigenous people is more crucial than ever. Indigenous people face unimaginable health, social, and political inequalities; therefore, there is a call to action that would create ripple effect change from practitioners and as a collective. In this article, the author explores how a two-eyed lens, a term coined by Elders Albert and Murdena Marshall (Iwama et al., 2009), answers this call by honouring Western and Indigenous world views and healing. What this article adds to the literature is how practitioners can implement two-eyed seeing, which starts with exploring the self, self-in-relation, and felt sense (Gendlin et al., 1968). This article describes this reflexive process in which counselling practitioners can develop a many-eyed lens in practice that honours Western and Indigenous therapeutic lenses and our own, in walking alongside Indigenous people. A many-eyed lens illustration with an Indigenous family is presented as a way to demonstrate and foster reconciliation, healing, and hope.